2009
DOI: 10.1590/s0100-40422009000500016
|View full text |Cite
|
Sign up to set email alerts
|

High encapsulation efficiency of sodium alendronate in eudragit S100/HPMC blend microparticles

Abstract: Recebido em 16/5/08; aceito em 12/12/08; publicado na web em 11/5/09The hydrophilic drug sodium alendronate was encapsulated in blended microparticles of Eudragit ® S100 and Methocel ® F4M or Methocel ® K100LV. Both formulations prepared by spray-drying showed spherical collapsed shape and smooth surface, encapsulation efficiencies of 85 and 82% and mean diameters of 11.7 and 8.4 µm, respectively. At pH 1.2, in vitro dissolution studies showed good gastro-resistance for both formulations. At pH 6.8, the sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
(27 reference statements)
0
6
0
1
Order By: Relevance
“…Results show that microencapsulation efficiency ranged from 85 to 89% among MD formulations and 98 to 99% for Hi‐cap100 formulations (Table ). This indicates acceptable encapsulation of flaxseed oil (Cruz, Assumpção, Guterres, & Pohlmann, ). The SEM images of MD and Hi‐cap100 formulations demonstrated that the spray‐dried particles possessed a combination of compact smooth, rough, and dented surface morphologies, whereas freeze‐dried formulations were less spherical and had many surface pores (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Results show that microencapsulation efficiency ranged from 85 to 89% among MD formulations and 98 to 99% for Hi‐cap100 formulations (Table ). This indicates acceptable encapsulation of flaxseed oil (Cruz, Assumpção, Guterres, & Pohlmann, ). The SEM images of MD and Hi‐cap100 formulations demonstrated that the spray‐dried particles possessed a combination of compact smooth, rough, and dented surface morphologies, whereas freeze‐dried formulations were less spherical and had many surface pores (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the encapsulation efficiency, a spectrophotometric method based on the derivatization of sodium alendronate with o-phthalaldehyde was used (Al Deeb et al, 2004;Cruz et al, 2009). A portion of microparticles equivalent to 10 mg of sodium alendronate was dissolved in 50 mL of 0.2 M NaOH and filtered using a filter paper (Whatman n° 40).…”
Section: Determination Of Yield and Encapsulation Efficiencymentioning
confidence: 99%
“…The experiments were carried out as described in our previous work (Cruz et al, 2009), in order to evaluate the gastroresistance at pH 1.2 and the sodium alendronate release profiles at pH 6.8.…”
Section: In Vitro Drug Release Studiesmentioning
confidence: 99%
“…The yield was calculated by the ratio of the experimental weight and the sum of the weights of all components, disregarding the water content. Encapsulation efficiency was determined spectrophotometrically at 333 nm using OPA as derivatizing agent (Cruz et al, 2009). Size and size distributions of microparticles were analyzed by laser diffractometry (Malvern Mastersizer, 2000 Inserir referência na parte reference, Malvern Instruments, UK).…”
Section: Preparation and Characterization Of Microparticlesmentioning
confidence: 99%